2008
DOI: 10.1097/yco.0b013e32830e6dc4
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic prescription practices in east Asia: looking back and peering ahead

Abstract: Future studies on prescribing trends of antipsychotics and antidepressants need to focus on children, adolescent and elderly patient populations, the impact of changing prescription trends and the long-term effects on patients and their caregivers, as well as pharmacogenetic factors, which can potentially pave the way for better and more individualized prescription of psychotropic drugs in east Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…[719] Besides clinical differences which may explain some of the variability in prescription patterns, the lower use of antidepressants found in the present study possibly reflects concerns of a possible switch to mania with antidepressants in bipolar disorder patients.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…[719] Besides clinical differences which may explain some of the variability in prescription patterns, the lower use of antidepressants found in the present study possibly reflects concerns of a possible switch to mania with antidepressants in bipolar disorder patients.…”
Section: Discussionmentioning
confidence: 82%
“…[6] A few surveys of prescription patterns of various psychotropics from Asian centers too are available. [47]…”
Section: Introductionmentioning
confidence: 99%
“…Thailand, in common with other Southeast Asian countries, has different socioeconomic, cultural, political, linguistic, health care, and reimbursement systems compared with other parts of the world 10. These results thus provide a valuable understanding of the role of paliperidone ER in the Thai context.…”
Section: Discussionmentioning
confidence: 87%
“…The socioeconomic, cultural, political, linguistic, health care, and reimbursement systems in Southeast Asian countries are diverse, as well as being different in comparison with other parts of the world 10. To investigate the efficacy of paliperidone ER in Southeast Asian patients with schizophrenia, the PERFEcT study was conducted from June 2007 to April 2009 11,12.…”
Section: Introductionmentioning
confidence: 99%
“…US business expansion in healthcare services has become a global phenomenon (Health and Medical 1997) and predominates over health concerns. For example,Tan and colleagues (Tan et al 2008;Chong & Tan 2010) found that factors such as insurance arrangements and the healthcare structure in a number of countries have become more significant in the prescription of psychotropic drugs than the drugs' effectiveness.…”
Section: Practice Pointsmentioning
confidence: 99%